PERANCANGAN SISTEM INFORMASI GEOGRAFIS PENYEBARAN PENYAKIT DEMAM BERDARAH DENGUE DI WILAYAH JOMBANG - Novi Dwesti Bahtiar; Agus Sifaunajah (SAINTEKBU, 2018)
One of the most common cases of disease in Indonesia is dengue hemorrhagic fever. Jombang region is one of the areas whose people are infected with dengue fever because every year there must be cases and cases that occur is also high. Various efforts have been made to prevent the spread of the disease. Among the 3M program (Drain, Closing, and Bury), fumigation (fogging) in each area that is endemic DHF. But still there are victims, even increasing from the years. From these problems is also required system capable of providing relief. With this problem then built a Web-Based Geographic Information System that can help people to know the actual spread of dengue fever. Geographic Information System is a collection of computer systems that store, process, manipulate, analyze geography data into quality information related to geographic objects. Within the Geographic Information System itself there are two important elements of Geographic Data used as a reference for attribute data, and the attribute data itself used to support spatial or geographical information. The design of the map to be displayed in this application using Google Maps API, while the methodology in the development of this system using waterfall method that includes system analysis, system design, system implementation and testing. In making this Web-based Geographic Information System uses MySQL as database to store the required data and use PHP as the programming language. The purpose of making Geographic Information System is to help Jombang District Health Office in providing information to the community about the spread of dengue fever so that it can reduce the number of patients each year. Keywords: Google Maps, GIS, Healthy, Dengue Fever.